Determination of tin content in canned guayabano and mango juices - Fonacier, Aileen B.; Acevedo, Teresita P. (1977)
This study was undertaken to determine the level of dissolved tin in canned fruit juice that have been stored for a period ranging from six to twenty-seven months. The method used for the analysis of the dissolved tin was the Zinc dithiol calometric method. pH determination, panel evaluation on metallic odor, taste, and particles and on general acceptability were also done. Visual examination of the interior of the cans was also included. The results showed that for both mango and guyabano juices, pH did not change, remaining in the range 3.80-4.00 throughout the storage period. Results of tin analysis showed a progressively increasing amount of tin dissolved in the juice with storage period. Results also showed that for the same length of storage time, guayabano juice contained a remarkably higher amount of dissolved tin than mango juice.
Appendices: leaves 38-70.
Thesis (B.S.)--University of the Philippines, Quezon City.
Typescript.
Keywords: Tin -- Analysis; Fruit juices, Canned; Tin containers